Solar energy policy directions for safer and cleaner development in Nigeria. (March 2021) - Ozoegwu, Chigbogu Godwin; Akpan, Patrick Udeme-obong
Abstract: This paper examines the Nigerian Solar Energy Policy (NSEP), as contained in the National Renewable Energy and Energy Efficiency Policy (NREEEP). It addresses the policy gaps and offers new directions for NSEP to develop further towards supporting safer and cleaner development of Nigeria. The formulation of the policy statements needs to take care of the adverse impacts of solar derived wastes on the environmental and human health. This need is quantitatively justified using projected data that was computed from interpolation and geometric series analyses to show that the share of solar PV-derived waste in Nigerian and global e-waste stream will get more significant going forward and, as such, must be accorded increased attention in e-waste monitoring policies in order to forestall worsening toxicity concerns. Security should be guaranteed for future utility-scale solar energy installations which could be vandalized by the host communities and lead to a repeat of the subsisting crises in the Nigerian oil and gas sector. Priorities on the various solar energy sources and technologies, on the basis of current socioeconopolitical realities in Nigeria, should dictate the chronology for both skills and market development. Regulatory/fiscal obligations/incentives must prioritize the target obligors/recipients according to their relative importance in the economy. Highlights: Nigeria's Solar Energy Policy lacks prioritization of technologies &market players. Policies on solar installations security & solar end-of-life management are missing. Policy recommendations are made towards closing the identified gaps. The shares of solar PV wastes in Nigerian and global e-waste streams are rising. Financing strategies for Nigerian PV waste management are proposed.